PENGARUH RELOKASI PEMUKIMAN KUMUH TERHADAP KUALITAS KESEHATAN LINGKUNGAN (STUDI KASUS KAMPUNG PULO JAKARTA TIMUR) - Irma Octalita Manurung; Charles Situmorang (JURNAL TECHLINK, 2022)
This study aims to determine the effect of slum relocation on environmental health quality (case study of Kampung Pulo, East Jakarta). The research method used is a survey with a quantitative approach. Data were analyzed using correlation and simple linear regression. This research was conducted on residents of Kampung Pulo slum relocation who were moved to West Jatinegara flats, East Jakarta, DKI Jakarta Province. This research was conducted from January to June 2022. The population of this study is 125 people of Kampung Pulo who were relocated to the West Jatinegara flats, East Jakarta. The sampling technique used is non-probability sampling, which is incidental sampling. The number of samples in this study using the Slovin formula of 95 Kampung Pulo people who were relocated to the West Jatinegara flats, East Jakarta. The results showed that the analysis obtained the regression equation = 32.185 + 0.603 X interpreted that every change in the Slum Settlement Relocation variable score (X) was 1 point, it can be estimated that the Environmental Health Quality score (Y) would change by 0.603 in the same direction with a constant of 32,185. The results of the t-test for tcount of 7.068 are greater than ttable (95) of 1.661 at = 0.05. The significance value (sig.) of 0.000 is smaller than = 0.05. This means that there is a positive (7.068) and significant (0.000) effect between Slum Relocation (X) on Environmental Health Quality (Y). The conclusion of the t test results is that there is a significant positive effect between Slum Relocation (X) on Environmental Health Quality(Y). This means that the more the relocation of slums to the West Jatinegara flats, East Jakarta, DKI Jakarta Province, the quality of environmental health will also increase. The correlation coefficient of the effect of Slum Settlement Relocation (X) on Environmental Health Quality (Y) (R) of 0.591 is included in the category of moderate relationship (Table 3.3: Medium = 0.40 – 0.599). The coefficient of determination is obtained from the R square value of 0.349. So 34.9% of the variance in Environmental Health Quality (Y) can be explained by the Slum Settlement Relocation variable (X). The remaining 65.1% is influenced by other variables outside the research, such as environmental sanitation, clean and healthy living behavior (PHBS), clean living attitudes and so on. Based on the results ofhypothesis testing, research findings show that there is a significant positive effect between Slum Settlement Relocation (X) on Environmental Health Quality (Y). Thus, the conclusion of the study is that the more the relocation of slums to the West Jatinegara rusunawa, East Jakarta, DKI Jakarta Province, the quality of environmental health will also increase